Melatonin protects INS-1 pancreatic β-cells from apoptosis and senescence induced by glucotoxicity and glucolipotoxicity. Issue 4 (3rd July 2020) - Lee, Yu Hee; Jung, Hye Sook; Kwon, Min Jeong; Jang, Jung Eun; Kim, Tae Nyun; Lee, Soon Hee; Kim, Mi-Kyung; Park, Jeong Hyun
ABSTRACT: Introduction: Melatonin is a hormone known as having very strong anti-oxidant property. Senescence is a biological state characterized by the loss of cell replication and the changes consisting of a pro-inflammatory phenotype, leading to Senescence Associated Secretory Phenotype (SASP) which is now regarded as one of the fundamental processes of many degenerative diseases. Increased cell division count induces cell senescence via DNA damage in response to elevated Reactive Oxygen Species (ROS). We wanted to test whether melatonin could reduce apoptosis and stress induced premature pancreatic β-cell senescence induced by glucotoxicity and glucolipotoxicity. Materials and method: Cultured rodent pancreatic β-cell line (INS-1 cell) was used. Glucotoxicity (HG: hyperglycemia) and glucolipotoxicity (HGP: hyperglycemia with palmitate) were induced by hyperglycemia and the addition of palmitate. The degrees of the senescence were measured by SA-β-Gal and P16 lnk4A staining along with the changes of cell viabilities, cell cycle-related protein and gene expressions, endogenous anti-oxidant defense enzymes, and Glucose Stimulated Insulin Secretion (GSIS), before and after melatonin treatment. Results: Cultured INS-1 cells in HG and HGP conditions revealed accelerated senescence, increased apoptosis, cell cycle arrest, compromised endogenous anti-oxidant defense, and impaired glucose-stimulated insulin secretion. Melatonin decreased apoptosis and expressions of proteins related to senescence, increase the endogenous anti-oxidant defense, and improved glucose-stimulated insulin secretion. Conclusion: Melatonin protected pancreatic β-cell from apoptosis, decreased expressions of the markers related to the accelerated senescence, and improved the biological deteriorations induced by glucotoxicity and glucolipotoxicity.